PENGARUH LITERASI KEUANGAN, PENGGUNAAN E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI TERHADAP EFEKTIVITAS KINERJA KEUANGAN UMKM DI BUKITTINGGI - Rahmadia Pipin; Andria Ningsih (Ensiklopedia of Journal, 2026)
This study aims to examine the influence of financial literacy, e-commerce utilization, and accounting information systems on the financial performance effectiveness of Micro, Small, and Medium Enterprises (MSMEs) in Bukittinggi City. MSMEs play an important role in the regional economy by creating employment opportunities, increasing community income, and supporting economic growth. However, many MSMEs still face challenges in financial management, digital technology utilization, and the implementation of accounting information systems, resulting in less effective financial performance. This study employed a quantitative approach using a survey method. The research population consisted of MSME owners in Bukittinggi City, with a sample of 61 respondents selected through purposive sampling based on predetermined criteria. Primary data were collected using a questionnaire with a five-point Likert scale and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4 software. The analysis included outer model and inner model evaluations. The findings indicate that financial literacy, e-commerce utilization, and accounting information systems have a positive and significant effect on the financial performance effectiveness of MSMEs in Bukittinggi City. This study is expected to contribute to the development of accounting knowledge and serve as a reference for policymakers in enhancing the digital competitiveness of MSMEs.Keywords: Financial Literacy, E-Commerce Utilization, Accounting Information Systems, Financial Performance Effectiveness, MSMEs, SmartPLS 4